EFFECTIVENESS AND COMMUNICATIONS ORGANIZATION LEADERSHIP STYLE ON THE PERFORMANCE OF EMPLOYEES AT HALEYORA POWER IN THE PANDEMIC COVID-19 - Agustriyana, Darwis; Septiana, M.; Dartanto, Rizal; Nurhayati, Yani; Jasmara, M. AdityaPutra; Azzahra, Sansabilla Arifa (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of the organization, customer satisfaction and contributing to the economy are part of performance. Leadership style and organizational communication are several factors that affect employee performance, because certain leadeship styles affect organizational communication and then affect performance. The purpose of this study was to determine the contribution of leadership style and organizational communication to performance, especially when working from home during the Covid- 19 pandemic at VI' Haleyora Power. This study uses a descriptive verification method with a sample size of 140 respondents. The results of the research on leadership style and organizational communication variables have an influence on employee performance at PT Haleyora Power. Meanwhile, simultaneously leadership style and organizational communication contribute to employee performance by 9.1 %.Suggestions should be that leaders are able to choose leadership styles and organizational communication that are in accordance with the conditions, especially amid limited ysical contact, during the Covid-19 pandemic.